Узгодження конфігурацій проектів кооперативів заготівлі молока із проектним середовищем - Тригуба, Анатолій Миколайович; Шарибура, Андрій Остапович; Шолудько, Петро Васильович; Рудинець, Микола Віталійович (НТУ "ХПІ", 2017)
Обґрунтовано потребу реалізації проектів функціонування та розвитку технологічно інтегрованих проектів виробництва, заготівлі та переробки молока. Запропоновано метод узгодження конфігурації проекту кооперативу заготівлі молока на території громади із проектним середовищем, який базуються на системно-ціннісному підході та імітаційному моделюванні. На підставі розробленого методу проведено узгодження конфігурації проекту кооперативу із заготівлі молока на території громади із проектним середовищем.

The condition analysis of dairy farming is done and the reasons for its degradation are revealed. The need of technologically integrated production systems projects, harvesting and processing of milk are substantiated. A scientific methodology and the method of project design of milk provision cooperative coordination in the community of the project environment, which are based on systematic-evaluative approach and simulation are proposed. The criterion for the definition of rational parameters of objects configuration for milk provision cooperative projects in the community system is the maximum value of their product. The monetary functioning assessment of the configuration object of cooperative milk provision projects in the community is done. On the basis of the proposed method we performed the coordination of project configuration of milk provision cooperative with the project environment of territory Zabolotsi community in Brody district of Lviv region.
Matching configurations projects of cooperative milk collection project environment
Keywords: управління; проект; конфігурація; кооператив; заготівля молока; цінність; моделювання; management; project; configuration; cooperative; milk provision; value; modeling